Microwave-induced self-organization in mineral systems. III. FeCl3 colloid (200 W; 2.45 GHz; 1 min) - Gradov, Oleg V; Gradova, Margaret A (PANGAEA, 2019)
Microwave-induced self-organization of membraneous structures with different morphology in hydrolized FeCl3 colloid (200 W, 2.45 GHz,1 min). The local MW treatment conditions and the precoursor layer thickness determine the type of emerging structures.
Keywords: Acageneite (β-FeOOH); Colloid particle self-assembly; Ferrihydrite; Goethite (α-FeOOH); Hematite; Hydrolytic polymerization and condensation; Lepidocrocite (γ-FeOOH); Maghemite; Self-organization in mineral systems